PENGARUH TINGKAT HUTANG DAN KEPEMILIKAN MANAJERIAL TERHADAP PERSISTENSI LABA PADA PERUSAHAAN MANUFAKTUR - Ganitri Putri, A.A Ayu; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2016)
This study aims to determine whether the debt level and managerial ownership affect the persistence of earnings. Sampling method is purposive sampling nonprobability sampling. Data analysis method used is simple regression and multiple linear regression. Simple regression analysis was used to measure the effect of the profit for the year to next year's earnings, while the multiple linear regression analysis to examine the effect of the level of debt and managerial ownership on earnings persistence. The population in this study consisted of 132 companies listed in the Indonesia Stock Exchange and the beginning of the observation period 2011-2013. Number of sample companies that meet the criteria of the sample is 21, a manufacturing company with 63 the data of observation. Based on the analysis and hypothesis testing, showed that the leverage s ignificantly influence the earnings persistence , while the managerial ownership has no effect on earnings persistence.
Keywords: Persistensi Laba, Tingkat Hutang, Kepemilikan Manajerial